Web-Man – a new software for web-based nutrient management in organic farming - Ostermaier-Welz, Aurelia; Luthardt, Marco; Donauer, Joseph; Stieber, Jette; Weckesser, Fabian; Albrecht, Marcus; Leßke, Frank; Hülsbergen, Kurt-Jürgen (Organic agriculture, 2025)
An essential prerequisite for the successful expansion of organic farming is an optimal nutrient supply to increase and stabilise yields and reduce the yield gap compared to conventional farming. To date, there is no practical software designed for organic farming, that supports farmers and advisors in soil organic carbon and nutrient management and maps all relevant nutrient flows at the farm level. The development of the nutrient management system Web-Man is intended to close this gap. The paper describes the development, architecture and functions of Web-Man. The system is designed for practical applications in agricultural enterprises and farm advisory services. Web-Man is being developed in a transdisciplinary approach involving software developers, agricultural scientists and future users. The participation of stakeholders enabled the detailed recording of the software requirements of users, researchers and nutrient specialists in government agencies. The Web-Man management system has a modular architecture. The core system comprises the user interface, interfaces for data import and export, and the farm model. The farm model records the structures and production processes of crop and livestock farming. Building on the data collection in the core system, specialized modules for organic farming can be utilized for organic fertilization requirement, humus balancing, on farm nutrient cycling, nitrogen turnover and nitrate leaching and decision support system for crop rotation management. The modules and algorithms take into account important aspects of organic farming, such as long-term fertilizer effects, organic carbon dynamics in soils, and nitrogen transfer in crop rotations. They are tailored to the conditions of organic farming. Web-Man is still under development. The core system and the subject-specific modules 3 Fertilizer requirement calculation (modules 3.1. and 3.2), 4 Nutrient balances (module 4.1), 5 Humus and carbon balances (modules 5.1, 5.2 and 5.3) are already available for end users. Further modules are to be completed by the end of 2025.